2009
DOI: 10.5194/angeo-27-861-2009
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency eigenmodes of thin anisotropic current sheets and Cluster observations

Abstract: Abstract. The eigenmodes of low frequency perturbations of thin anisotropic current sheets with a finite value of the normal magnetic field, are investigated in this paper. It is shown that two possible polarizations of symmetric and asymmetric modes (sausage and kink) exist where the growth rate of instabilities is positive. In addition, we demonstrate that a tearing instability might have a positive growth rate in thin anisotropic current sheets. The class of relatively fast wavy flapping oscillations observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 27 publications
(41 reference statements)
0
49
0
1
Order By: Relevance
“…Figure 7 shows a typical value of | B Z / X|∼0.5 nA/m 2 and B X / Z∼40 nA/m 2 and using the observed proton number density 0.4/cc, we obtain ω f or γ f to be 0.14 corresponding to a period/growth time of 34 s. This is a comparable value of the estimated flapping period before. Kink-mode oscillation was also obtained in Zelenyi et al (2009) in a several-ion scale thin current sheet, which was the case for the observed current sheet. The theoretical prediction of the phase velocity being comparable to the drift velocity, and the wavelength to be comparable to the thickness of the current sheet is fulfilled in this observation within a factor of 6.…”
Section: Discussion and Summarymentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 7 shows a typical value of | B Z / X|∼0.5 nA/m 2 and B X / Z∼40 nA/m 2 and using the observed proton number density 0.4/cc, we obtain ω f or γ f to be 0.14 corresponding to a period/growth time of 34 s. This is a comparable value of the estimated flapping period before. Kink-mode oscillation was also obtained in Zelenyi et al (2009) in a several-ion scale thin current sheet, which was the case for the observed current sheet. The theoretical prediction of the phase velocity being comparable to the drift velocity, and the wavelength to be comparable to the thickness of the current sheet is fulfilled in this observation within a factor of 6.…”
Section: Discussion and Summarymentioning
confidence: 97%
“…The opposite B X variation below and above the equator suggests a sausage mode with a period of 2-3 min for this variation. Theoretical models of low-frequency kink-mode oscillation of a current sheet with finite B Z have been presented in several papers (Golovchanskaya and Maltsev, 2005;Erkaev et al, 2008;Zelenyi et al, 2009) stimulated by Cluster current sheet observations in the mid tail (e.g., Sergeev et al, 2003;Runov et al, 2005a). Compared to the previous kink mode observations by Cluster (Sergeev et al, 2003;Runov et al, 2005b;Zhang et al, 2005;Volwerk et al, 2008) in the mid-tail in a relatively thicker current sheet and during predominantly quiet intervals, the oscillation shown in this study have higher frequency, observed at a thinner current sheet but more closer to the Earth and associated with clear dipolarization and fast flows.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In majority of cases current density profiles were distinctly different from the classical Harris shape (Harris, 1962) and were categorized as embedded, bifurcated, or asymmetric (Asano et al, 2005;Runov et al, 2006;Nakamura et al, 2006;Thompson et al, 2006). Another unexpected feature was abundance of strongly tilted (in the YZ GSM plane) sheets with rather variable profiles (Sergeev et al, 2004;Petrukovich et al, 2006), which most likely represent nonstationary structures (Malova et al, 2007;Petrukovich et al, 2008;Zelenyi et al, 2009;Erkaev et al, 2009) and often cannot be explained by motion of the sheet as a whole. A variety of TCS models available now is also quite wide (Kropotkin and Domrin, 1996;Schindler and Birn, 2002;Sitnov et al, 2006;Zelenyi et al, 2004;Yoon and Lui, 2004) (see Sect.…”
Section: Introductionmentioning
confidence: 99%
“…Flapping, how it is recognised now, is one of the most widespread types of CS activity (e.g. Zhang et al, 2002;Sergeev et al, 2004). However, other manifestations of CS dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sergeev et al, 1998;Runov et al, 2012), investigate Hall electric field configuration in CSs (Wygant et al, 2005;Vasko et al, 2014), and test numerical models of CS instability (e.g. Karimabadi et al, 2003b;Sitnov et al, 2006;Zelenyi et al, 2009;Nakamura et al, 2009). The opportunity of four-spacecraft measurements of magnetic field provided by the Cluster mission was actively used to investigate details of the CS flapping (Runov et al, 2005a;Petrukovich et al, 2006Petrukovich et al, , 2008Rong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%